The Role of Appropriate Technology in Enhancing Efficiency and Production in Livestock and Agriculture Sectors: A Systematic Review in Indonesia: Peran Teknologi Tepat Guna dalam Meningkatkan Efisiensi dan Produksi di Sektor Peternakan dan Pertanian: Tinjauan Sistematik di Indonesia - Permadi , I Gede Wempi Dody Surya; Novita, Risqa (Universitas Muhammadiyah Sidoarjo, 2023)
Indonesia's agricultural sector significantly contributes to the country's foreign exchange earnings through agricultural product exports, including livestock, plantations, and ornamental plants. However, addressing the weaknesses in free-range chickens and other livestock is crucial to sustain population levels and meet organoleptic needs. This systematic review aims to explore appropriate technology development in the livestock and agriculture sectors, focusing on feed processing, animal husbandry management, and increased production. The review includes articles from journals, books, and theses, with data sourced from Google Scholar and Pop8win using specific keywords. The results highlight the effectiveness of appropriate technology in improving feed efficiency, labor efficiency, and production in livestock and agriculture. Consequently, further research is recommended to enhance the application of appropriate technology, contributing to the sustainable development of the agriculture sector in Indonesia. Highlights: The systematic review reveals that appropriate technology positively affects feed efficiency, labor efficiency, and production in Indonesia's livestock and agriculture sectors. The application of appropriate technology in feed processing and animal husbandry management leads to significant improvements in productivity. Addressing weaknesses through appropriate technology can contribute to the sustainable development of the agriculture sector in Indonesia.